Review on Gold Nanoparticles and Their Applications as Smart Sensing Devices - Fuad Hilmi, M.S.; Azhari, S.; Abu Hassan, M.H. (Universiti Sains Islam Malaysia, 2024)
Gold nanoparticles (GNPs) are attractive materials that are widely used in many fields due to the unique optical, physical and chemical properties. Recently, many advancements were made in biomedical applications as a smart sensing device with better biocompatibility in disease diagnosis. GNPs could be prepared and conjugated with many functionalizing thorough chemical and biosynthesis. Qualitative analysis on several related articles manage to investigate the synthesis of gold nanoparticles, including surface functionalization with a wide range of molecules to improve the applications of gold nanoparticles in targeting drugs in various cancers, gene therapy and other diseases.